A Quay Crane System that Self-recovers from Random Shocks - LIM, Yun Fong (Institutional Knowledge at Singapore Management University, 2015)
The main challenge for a container terminal is to maximize its throughput using limited resources subject to various operational constraints under uncertainty. Traditional methods try to achieve this through an optimized plan by solving a quay crane scheduling problem; but the plan may become obsolete or infeasible after shocks (changes in the system due to uncertainty). To respond to shocks these methods require frequent re-planning, which increases the operations cost. We propose a new method to counter this. Instead of creating plans, we develop an operating protocol to respond to shocks without re-planning. Under this protocol, each quay crane along a berth follows simple rules to serve vessels that arrive continuously in time. If the system is configured properly, it always spontaneously recovers to its efficient form after a random shock. The average throughput of the system operating on its efficient form is very near its full capacity if the crane travel time per bay is relatively short. This self-recovery is robust even under a sequence of shocks as the system persistently restores its throughput after each shock. Most importantly, this is accomplished without complex computation.